AN ETHICAL ISSUE OF SELECTIVE REDUCTION FOR MULTIFETAL-PREGNANCIES VERSUS SANCTITY OF LIFE - Theresia, Siwi Ikaristi Maria (Universitas Respati Yogyakarta, 2017)
Background: Selective reduction for multi-fetal pregnancies is a part of reproductive technologywhich developed to help infertile couples have healthy babies. That treatment is controversialbecause the purpose of the action is to improve quality of life but it is contrary with sanctity of life.The point about sanctity of life from various religions to be a moral and it is believed of everyone.Objective: This paper aims to explore the associated ethical issues of quality of life versus sanctity oflife as well as some benefits and harms of selective reduction for the mother, fetuses and community.Method: Literature search of articles between 1996-2016. Results: In vitro fertilization is a commonresult of multiple gestations. In order to get healthy baby/babies, in the United Stated selectivereduction for fetus/fetuses who have bad condition should be done, even though it is a risky treatment.On the other hand, it is contrary with sanctity of life views from four religions including Catholic,Islam, Buddhism and Hinduism. Conclusion: The procedure of selective reduction has benefits andharms to both mother and fetus/fetuses. It is related to morbidity and mortality. The treatment alsobrings the impact for community. This is a difficult decision for couples because their desire is incontrast to moral principle views.